Strategi Pengembangan Objek Wisata Alam Kapalo Banda Taram Kabupaten Lima Puluh Kota dalam Peningkatan Jumlah Pengunjung Ditinjau dari Perspektif Manajemen Bisnis Syariah - Nhada Haresky; Zulhelmi Zulhelmi (ARZUSIN, 2026)
Although tourism development strategies have received attention in various studies, studies that specifically discuss strategies for developing natural tourist attractions to increase visitor numbers from the perspective of Sharia business management in a local context remain limited. This study aims to formulate a development strategy for the Kapalo Banda Taram tourist attraction, Lima Puluh Kota Regency, to increase visitor numbers based on a Sharia business management approach. This study employed a qualitative approach with a case study design, involving informants consisting of tourist attraction managers, the Wali Nagari, surrounding community members, and visitors selected purposively. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using SWOT analysis. The results showed that the Kapalo Banda Taram tourist attraction has strengths in the form of natural potential that remains unspoiled and a beautiful environment, but faces weaknesses in terms of infrastructure, management, and promotion. The available opportunities include increasing interest in nature tourism and government support, whereas the threats faced include competition from other destinations and weather factors. Management efforts have been made, but they have not yet had a significant impact on increasing visitor numbers. These findings contribute to the development of strategic management theory and Sharia business management in the tourism sector. This study concludes that improving management, providing facilities, and strengthening promotion strategies based on Sharia principles are important aspects in developing tourist attractions. The practical implications of this study are intended for managers and local governments, while also opening opportunities for further research on digital promotion and Sharia-based tourism management.